2018
DOI: 10.1159/000484980
|View full text |Cite
|
Sign up to set email alerts
|

Transient Receptor Potential Ankyrin 1 and Substance P Mediate the Development of Gastric Mucosal Lesions in a Water Immersion Restraint Stress Rat Model

Abstract: Background: Activation of substance P (SP) contributes to the development and maintenance of gastric lesions, but the mechanisms underlying the release of SP and SP-mediated damage to the gastric mucosa remain unknown. Transient receptor potential ankyrin 1 (TRPA1) is expressed in SP-positive neurons in the dorsal root ganglion (DRG) and stomach of rats. We hypothesized that water immersion restraint stress (WIRS) may activate and sensitize TRPA1 in DRG neurons, subsequently inducing the release of SP from DRG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…It has been reported that substance P may initiate the earliest changes observed in blood-brain barrier permeability (40). In addition, it has also been documented that TRPA1 mediates the development of gastric mucosal and duodenal lesions in a water immersion restraint stress rat model by promoting the release of substance P (22,41). Since TRPA1 is involved in Ca 2+ influx and increases in tight junction permeability (42), TRPA1 may contribute to damage in epithelial barrier function by regulating oxidative stress induced by stress.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that substance P may initiate the earliest changes observed in blood-brain barrier permeability (40). In addition, it has also been documented that TRPA1 mediates the development of gastric mucosal and duodenal lesions in a water immersion restraint stress rat model by promoting the release of substance P (22,41). Since TRPA1 is involved in Ca 2+ influx and increases in tight junction permeability (42), TRPA1 may contribute to damage in epithelial barrier function by regulating oxidative stress induced by stress.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we chose a rabbit extracellular TRPA1 antibody for several reasons: (1) this antibody has been well characterized by the vendor, demonstrating a high specificity against an epitope (NSTGIINETSDHSE) corresponding to amino acid residues 747 to 760 in the first extracellular loop of TRPA1 ( Figure 1a); (2) the specificity has been verified in TRPA1 knockout tissue; 38 and (3) it consistently detects TRPA1 expression by IHC or immunoblot from DRGs and from nonneuronal tissues. 19,[36][37][38]40,[53][54][55][56][57][58][59][60][61][62][63] We also tested the specificity of this antibody in the detection of TRPA1 expression. By immunoblot, the antibody revealed a clean band at $120 KDa as the target protein in the homogenates of the DRGs from adult rats, and preincubation with excess immunogenic peptide completely eliminated the band (Figure 1b).…”
Section: Trpa1 Is Expressed In Primary Sensory Neurons Sgcs and Scsmentioning
confidence: 99%
“…Propolis extracts usually have an intense odor and pungent taste. The pungent taste accounts for APC ligation to transient receptor potential channel ankyrin 1 (TRPA1) [324], which are abundant in the stomach and involved in stress-induced gastric mucosal lesions [325]. Hence, one should make efforts to exclude the “side effects” of propolis by using more adequate controls.…”
Section: Perspectivesmentioning
confidence: 99%